Circulating nucleic acids as biomarkers in cancer patients - Pantel, Klaus (Henry Stewart Talks, 2012)
Circulating Nucleic Acids, Advantages of Serum/Plasma DNA vs. Tumor Tissue DNA, Circulating DNA in patients with benign disease and malignant tumors, Circulating microRNAs in cancer patients, Associations between Circulating Tumor Cells and cell-free tumor DNA in cancer patients